Hubungan Stress dan Waktu Pengasuhan dengan Perkembangan Bahasa pada Anak Usia 3 – 5 Tahun - Yusnika Damayanti; Putri Permata Sari; Yusnaini Yusnaini (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between stress and parenting time with language development in children aged 3-5 years. The method used is a descriptive correlation with the cross-sectional approach. The results showed a significant relationship between stress and parenting time and the language development of children aged 3-5 years, where the p-values were 0.027 and 0.006. In conclusion, stress experienced by parents and non-parenting time is related to child development. So, it is suggested that health workers educate the growth and development of toddlers and practice relaxation techniques so that mothers can deal with stress independently. Keywords: Children's Language Development, Stress, Parenting Time